Turnês de Guerrilha: as estratégias de empreendedorismo musical nos circuitos do rock no exterior - Luiza Bittencourt (Ciências Sociais Unisinos)
This article aims to analyze the strategies employed by Brazilian rock bands with regard to touring abroad from an entrepreneurship perspective (Schumpeter, 1982; Timmons, 1985; Dornelas, 2007), in order to understand how the formation of an international au- dience occurs. In this context, we seek to discuss the concept of “independent musician” and introduce the notion of “entrepreneurial musician”. The methodology used involved bibliographical revision, interviews with a musician from the band Autoramas, as well as monitoring of social networks and the press in matters related to the tours of such group.